The in vitro and in vivo protective effects of tannin derivatives against Salmonella enterica serovar Typhimurium infection. (August 2017) - Reyes, Alisha Wehdnesday Bernardo; Hong, Tae Gyu; Hop, Huynh Tan; Arayan, Lauren Togonon; Huy, Tran Xuan Ngoc; Min, Wongi; Lee, Hu Jang; Lee, Kang Seok; Kim, Suk
Abstract: In this study, we investigated the protective effects of tannin-derived components, gallic acid (GA) and tannic acid (TA), in vitro and in vivo against Salmonella infection in mice. Both GA and TA showed antibacterial effects against Salmonella ( S. ) Typhimurium as well as inhibitory effects on the adherence, invasion, and intracellular growth of the pathogens in macrophages. Following a lethal dose of Salmonella infection in mice, reduced virulence in both GA- and TA-treated groups was observed based on reduced mortality rates. In the non-infected groups, the average weights of the spleens and livers of GA- or TA-treated mice were not significantly different with the control group. In addition, the average weights of these organs in all of the Salmonella -infected groups were not significantly different but the numbers of bacteria in the spleens and livers in both GA- and TA-treated mice were significantly reduced. The levels of cytokine production in non-infected mice revealed that GA-treated and TA-treated mice elicited an increased level of IFN-γ, and both IFN-γ and MCP-1, respectively, as compared with the PBS-treated group. These findings highlight the potential of GA and TA as alternatives for the treatment of salmonellosis and as supplements to conventional antimicrobial food additives. Highlights: Gallic acid (GA) and tannic acid (TA) showed antibacterial effects against S. Typhimurium. GA and TA showed a treatment effect against S. Typhimurium infection in a mouse model. GA-treated and TA-treated mice elicited an increased level of IFN-γ, and both IFN-γ and MCP-1, respectively. GA and TA could be used as potential alternatives for the treatment of salmonellosis.